Pengaruh Variasi Bahan Tambah Abu Sekam Padi dan Zat Adiktif Bestmittel 0,5% Terhadap Kuat Tekan Beton Mutu Tinggi - Nugraha, Yoga; Prayuda, Hakas; Saleh, Fadillawaty (Semesta Teknika, 2017)
Concrete is the mixture of portland cement or hidrolyc cement, fine aggregate, coarse aggregate and water with or without additional mixture to form solid mass. The use of cement makes the concrete price more expensive, so an innovation is needed which to be use natural additive, such as rice husk ash. This research was carried by decreasing the use of cement that was replaced by rice husk ash with the variation 5%, 10%, and 15%, and 0.5% additive material (bestmittel) of the cement. Cylinder samples with the diameter of 15 cm and heigth of 30 cm were tested at the age of 28 days. The result of this research shows that the compresssive strength of the concrete was affected by the additional of rice husk ash (RHA) and additive material (bestmittel), which decrease the compressive strength every additional rice husk ash. The use of rice husk ash and bestmittel on the concrete for 3 variation which were 5 % ; 10% ; and 15% with the additive (bestmittel) 0.5%Â obtained compressive strength were 32,23MPa; 31,84MPa and 27,71MPa.